Patient privacy from the perspectives of perioperative nurses: a qualitative study - Zahra Royani; Mohammad Heidari; Zahra Sabzi; Soheyla Kalantari; Maryam Chehrehgosha; Ghorban Mohammad Kouchaki; Mahnaz Shahmiri (Shahrekord University of Medical Sciences, 2021)
Background and aims: Privacy is one of the most basic rights of patients. Privacy protection in the complex and stressful environment of operating room needs special attention. The aim of the study was to explore patient privacy from the perspectives of perioperative nurses. Methods: This descriptive qualitative study was conducted in 2016 on fifteen perioperative nurses purposefully selected from a teaching hospital in Gorgan, Iran. Data were collected via in-depth semi-structured interviews and were analyzed via conventional content analysis. Results: Participants' experiences of patient privacy came into five main categories, namely body covering, effective communication with patient, comfort provision, care provision by same-gender healthcare providers, and ensuring patient safety. These categories were grouped into the main theme of safety-oriented care. Conclusion: This study provides a better understanding about patient privacy in operating room and shows patient privacy as a basic need of patients. Policies and strategies are needed to improve patient privacy protection in operating room.